A class of nonlinear internal models for global robust output regulation problem. (22nd April 2014) - Lu, Maobin; Huang, Jie
Summary The global robust output regulation problem of nonlinear systems in output feedback form has been studied via a linear internal model. In this paper, we study the same problem using a class of nonlinear internal models. An advantage of nonlinear internal models is that it exists even when the system contains nonpolynomial nonlinearity and the exosystem is nonlinear. Thus, the result of this paper applies to a larger class of nonlinear systems and a larger class of exosystems. Copyright © 2014 John Wiley & Sons, Ltd.